Students’ Psychological Factor in Learning from Home during Pandemic Covid-19: Identifying the Impact - Bahrun Amin; Farisha Andi Baso; Linda Pajarwati (STAI Hubbulwathan Duri, 2023)
Since the COVID-19 attack in Indonesia, schools have switched from face-to-face learning to learning at home. Due to the challenges of social distancing training, the classroom has been relocated online. The students' sense of self-worth is impacted. The study indicated that students' mental health negatively affects their ability to learn English at home during the COVID-19 pandemic. It is evident from the fact that the questionnaire data on the five psychological components of English language learners is highly relevant. Aspects of one's personality that were shown to be significant were as follows: intelligence (74.37%), motivation (62.29%), interest (64.79%), emotion (70.20%), and attitude (63.125%). Students' comments in the interviews indicate that independent study is ineffective. Students struggle to learn due to a number of factors, including a lack of time to devote to online study, an inability to communicate with classmates in real-time, an unstable connection, challenging subject matter, an abundance of assigned reading, and a preference for in-person instruction. The psychological element of students learning English at home during the COVID-19 pandemic can thus be said to have a very harmful effect.